ROSEs (Rapid on‐site evaluations) to our patients: The impact on laboratory resources and patient care. Issue 10 (3rd July 2013) - da, Gilda
<x xml:space="preserve">Abstract</x> The study by Collins et al published in this issue of Cancer Cytopathology sheds light on financial costs and patient safety as important indicators in evaluating the impact of the introduction of rapid on‐site evaluation (ROSE) in clinical routine.